Elemental site occupancy in the L12 A3B ordered intermetallic phase in Co-based superalloys and its influence on the microstructure. (15th January 2019) - Pandey, P.; Makineni, S.K.; Samanta, A.; Sharma, A.; Das, S.M.; Nithin, B.; Srivastava, C.; Singh, A.K.; Raabe, D.; Gault, B.; Chattopadhyay, K.
Abstract: We explore the effects of the elemental site occupancy in γ′-A3 B (L12 ) intermetallic phases and their partitioning across the γ/γ′ interface in a class of multicomponent W-free Co-based superalloys. Atom probe tomography and first principles density functional theory calculations (DFT) were used to evaluate the Cr site occupancy behavior in the γ′ phase and its effect on the γ/γ′ partitioning behavior of other solutes in a series of Co-30Ni-10Al-5Mo-2Ta-2Ti-XCr alloys, where x is 0, 2, 5, and 8 at.% Cr, respectively. The increase in Cr content from 0 to 2 to 5 at.% leads to an inversion of the partitioning behavior of the solute Mo from the γ′ phase ( K M o > 1 ) into the γ matrix ( K M o < 1 ) . At 5 at.% Cr, the Cr also has a preference to replace the excess anti-site Co atoms from the B-sites. At 8 at.% Cr, the Cr develops an additional preference to replace Co atoms from the A-sites. These compositional changes in the phases and the site partitioning behavior in the γ′ phase are accompanied by an overall decrease in the lattice misfit (δ) across the γ/γ′ interfaces as measured by high-resolution X-ray diffraction at room temperature. The reduction in misfit triggers a change in morphology of the γ′ phase from cuboidal (δ ∼ +0.48% at 0 at.% Cr) to round-cornered (δ ∼ +0.34% at 5 at.% Cr) to spheroidal shaped (δ ∼ +0.19% at 8 at.% Cr) precipitates. We also observed an increase in the solvus temperature from 1066 °C to 1105 °C when adding 5 at.% Cr to the alloy. These results on the effects of Cr in Co-base superalloys enable tuning the microstructure of these alloys and widening the alloy spectrum for designing improved high temperature alloys. Graphical abstract: Image 1